Exploring a P300 Brain-Computer Interface Based on Three Different RSVP Paradigms - Ron-Angevin, Ricardo; Abadie, Maëlle; Cloarec, Maëlle; Filosa, Martin; Jouault, Maurine; Pestre-Sorge, Quentin; Lespinet-Najib, Véronique; André, Jean-Marc; García, Liliana (Birgit Gersbeck-Schierholz, Leibniz Universität Hannover, Germany, 2019)
A BCI Speller is a typical Brain-Computer Interface (BCI) system for communication purpose. This technology can provide users with severe motor disability with an assistive device controlled by brain activity. In the present preliminary study we investigated, in five subjects, the performance and the Information Transfer Rate (ITR) based on three different Rapid Serial Visual Presentation (RSVP) paradigms to control a BCI speller. The variants of the three paradigms were the stimuli presented: letters, images and famous faces. These preliminary results showed that performance can increase when using an RSVP paradigm based on images, and ITR can improves when using the images and the famous faces paradigms.
Keywords: Brain-Computer Interface (BCI); P300; Speller; Stimuli; RSVP Paradigm